Respostas

2013-07-08T21:56:53-03:00
Y= x2+2x
y=(-3) -3.2+2.(-3)= -6+(-6)=-12
y=(-2) -2.2+2.(-2)= -4+(-4)= -8
y=(-1) -1.2+2.(-1)= -2+(-2)= -4
y=(0) 0.2+2.0= 0+0=0
y= (1) 1.2+2.1= 2+2=4
y= (2) 2.2+2.2=4+4=8
y= (3) 3.2+2.3= 6+6=12

Y=x2-2x+1

y=(-3) (-3).2-2.(-3)+1= -6 - (-6) +1= 0 +1= 1
y= (-2) (-2).2-2.(-2)+1= -4-(-4)+1= 0+1=1
y=(-1) (-1).2-2.(-1)+1= 0 +1=1
y=(0) 0.2-2.0+1=0+1=1
y=(1) 1.2-2.1+1=0+1=1
y=(2) 2.2-2.2+1=0+1=1
y=(3) 3.2-2.3+1=0+1=1

y=x2

y= (-3) (-3).2= -6
y= (-2) (-2).2= -4
y= (-1) (-1).2= -2
y= (0)  (0).2=0
y= (1)  1.2=2
y= (2)   2.2=4
y=(3)    3.2 =6

y=-x2+1

y(-3) -(-3).2+1=3.2+1=7
y=(-2) -(-2).2+1= 2.2+1=5
y=(-1) -(-1).2+1=1.2+1=3
y=(0)   -0.2+1=0+1=1
y=(1)  -1.2+1= 1+1=2
y=(2)   -2.2+1= -4+1=-3
y=(3)   -3.2+1=-6+1=-5


espero ter te ajudado ok!
1 5 1